RAS ACADEMICIANS AND CORRESPONDING MEMBERS OF RAS ELECTED BY THE GENERAL MEETING OF MEMBERS OF RAS ON OCTOBER 27-28, 2016 BY DEPARTMENTS OF PHYSIOLOGY AND MEDICINE - article editorial (Рациональная фармакотерапия в кардиологии)
.